Molecular recognition of surface-immobilized carbohydrates by a synthetic lectin - Rauschenberg, Melanie; Fritz, Eva-Corrina; Schulz, Christian; Kaufmann, Tobias; Ravoo, Bart Jan (Beilstein Journal of Organic Chemistry, 2014)
The molecular recognition of carbohydrates and proteins mediates a wide range of physiological processes and the development of synthetic carbohydrate receptors (“synthetic lectins”) constitutes a key advance in biomedical technology. In this article we report a synthetic lectin that selectively binds to carbohydrates immobilized in a molecular monolayer. Inspired by our previous work, we prepared a fluorescently labeled synthetic lectin consisting of a cyclic dimer of the tripeptide Cys-His-Cys, which forms spontaneously by air oxidation of the monomer. Amine-tethered derivatives of N-acetylneuraminic acid (NANA), β-D-galactose, β-D-glucose and α-D-mannose were microcontact printed on epoxide-terminated self-assembled monolayers. Successive prints resulted in simple microarrays of two carbohydrates. The selectivity of the synthetic lectin was investigated by incubation on the immobilized carbohydrates. Selective binding of the synthetic lectin to immobilized NANA and β-D-galactose was observed by fluorescence microscopy. The selectivity and affinity of the synthetic lectin was screened in competition experiments. In addition, the carbohydrate binding of the synthetic lectin was compared with the carbohydrate binding of the lectins concanavalin A and peanut agglutinin. It was found that the printed carbohydrates retain their characteristic selectivity towards the synthetic and natural lectins and that the recognition of synthetic and natural lectins is strictly orthogonal.
Keywords: carbohydrates; lectins; molecular recognition; microarrays; multivalent glycosystems; peptides